Accommodating the Role of Central Axis Lecturers through the Total Institutional Method in CB Higher Education - Rafdi, M. A. (Journal of Education Research and Evaluation, 2021)
The tendency of total institutions is marked through starting from the stages and processes of formation to the birth of the BP3K, which these stages and processes include Compertmentalization The problems that occur at the Citra Buana Indonesia College are the potential possessed by creative functional lecturers whose creativity is not channeled and the potential for creative structural lecturers whose creativity is not channeled into their jobs as structural in Higher EducationCitra Buana Indonesia Sukabumi, where they have the potential, namely the strength of values at the A4 level and are equally pro-active in addressing the situation of the Citra Buana Indonesia College which is considered to tend to be passive in responding to the development of Tri Dharma Perguruan Tinggi and MBKM. The research method used is descriptive method. Is to explore and explore the problem to produce a holistic description of the problem. From the research results that they are termed the middle axis lecturer. then they are grouped at once combined into a container. A container that is in accordance with their characteristics and character is a manifestation with a tendency towards total institutions. the manifestation of the tendency of the total institution to be named BP3K, namely the Field of Curriculum Development and Supervision, Resocialization, Isolation, very binding rules, tight control, the role of centralized regulator / coach. BP3K activities in the form of studies and training as well as regeneration of member resources in the field of functional competencies in the realm of Tri Dharma Perguruan Tinggi. The total institutional element that contributes the most to the benefits and impacts of BP3K when compared to other elements is the element of isolation and the strength of the supervisor. the implication of the research results, that through BP3K is to make the Citra Buana Indonesia College as the organizer of basic character training for lecturers of universities in West Java and Banten, information and appreciation for two tutors from BP3K as tutorial implementersBasic Characteristics.bP3K is also used as an accreditation consultant as well as a training center for various achievements and expertise for the Citra Buana Indonesia College.